2012
DOI: 10.1111/j.1467-9809.2011.01169.x
|View full text |Cite
|
Sign up to set email alerts
|

The Ritual Year of Athena: The Agricultural Cycle of the Olive, Girls' Rites of Passage, and Official Ideology

Abstract: Through the ritual year of ancient Athens, many festivals were dedicated to Athena. The Panathenaia was the most important festival. It has been regarded as a political festival, but the importance of agriculture is also illustrated through the offerings and rituals carried out during this main festival dedicated to the Goddess of the olive crop. All Athena's festivals were related to the olive, the third main crop of the Athenians, and protected by her, as her festivals were celebrated in the crucial period f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This finding offers the possibility that an image showing small round balls being raked out of a kiln by an attendant may be olive pits, not only charcoal as suggested in the literature. 38 Pomace would have been easily available in Athens given the cultural and economic importance of its olive oil industry (Haland 2012) and the ability to use materials that would otherwise have been wasted would have perhaps been a cost-savings for potters. In our own experimentation, we tested wet pine boughs, charcoal, cow manure, olive pits and olive pomace and found that each material had not only its own distinct ability (or inability) to hold heat but also produced its own distinctive 37 Cuomo Di Caprio (1984) even mentions the use of cut up horses' hooves as a possibility for fuel.…”
Section: The Third Sensory Phase: the Smell And Taste Of Black Potsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding offers the possibility that an image showing small round balls being raked out of a kiln by an attendant may be olive pits, not only charcoal as suggested in the literature. 38 Pomace would have been easily available in Athens given the cultural and economic importance of its olive oil industry (Haland 2012) and the ability to use materials that would otherwise have been wasted would have perhaps been a cost-savings for potters. In our own experimentation, we tested wet pine boughs, charcoal, cow manure, olive pits and olive pomace and found that each material had not only its own distinct ability (or inability) to hold heat but also produced its own distinctive 37 Cuomo Di Caprio (1984) even mentions the use of cut up horses' hooves as a possibility for fuel.…”
Section: The Third Sensory Phase: the Smell And Taste Of Black Potsmentioning
confidence: 99%
“…This finding offers the possibility that an image showing small round balls being raked out of a kiln by an attendant may be olive pits, not only charcoal as suggested in the literature. 38 Pomace would have been easily available in Athens given the cultural and economic importance of its olive oil industry (Haland 2012) and the ability to use materials that would otherwise have been wasted would have perhaps 37 Cuomo di Caprio (1984) even mentions the use of cut up horses' hooves as a possibility for fuel. 38 See the Penteskouphia plaque currently in the collection of the Louvre, accession number MNB 2856.…”
Section: The Third Sensory Phase: the Smell And Taste Of Black Potsmentioning
confidence: 99%
“…Barrera-Bassols and Toledo (2005) discuss the complex entanglement of beliefs, knowledge and landscape management by presenting aspects of the Yucatec Mayan spiritual landscape and the sacred dimension as a key contributor to their social-ecological resilience. Håland (2009Håland ( , 2012Håland ( , 2015 has discussed ritual and agricultural yearly cycles by comparing modern and ancient Greek festivals, and illustrated the importance to farmers of fertility magic to ensure good harvests both in modern and ancient Greece. Salmón (1999) shows how the physical, social and mental health of northern Mexico Rarámuri are closely related to their cycle of ceremony.…”
Section: Introductionmentioning
confidence: 99%
“…The Mediterranean has affixed great importance to the cultural and religious connotations of olive trees and oil. Greek mythology regards the olive tree on the Acropolis of Athens as sacred, which Athena planted to create the order against the maritime dominance of Poseidon [10], and it was central to rituals during the Panathenaia festival [11]. Roman deities Mars and Pax are depicted holding an olive branch as a symbol of peace and order.…”
Section: Introductionmentioning
confidence: 99%